Formation of microbial inhibitors in steam-explosion pretreatment of softwood impregnated with sulfuric acid and sulfur dioxide. (August 2018) - Martín, Carlos; Wu, Guochao; Wang, Zhao; Stagge, Stefan; Jönsson, Leif J.
Highlights: Microbial inhibitors in steam-pretreated softwood were characterized. Effects of impregnating agents and temperature on inhibitor formation were compared. Storage of pretreated biomass affects the concentrations of some inhibitors. Among the inhibitors, the toxic effects of formaldehyde were the most significant. Abstract: Wood chips of Norway spruce were pretreated by steam explosion at 195–215 °C after impregnation with either sulfuric acid (SA) or sulfur dioxide (SD). The effects of different pretreatment conditions on formation of microbial inhibitors were investigated, and the inhibitory effects on yeast of pretreatment liquids and of specific inhibitors that were found in the pretreatment liquids were elucidated. Whereas the concentrations of most inhibitors increased with increasing pretreatment temperatures, there were exceptions, such as formaldehyde and p -hydroxybenzaldehyde. The highest concentration of each inhibitor was typically found in SD-pretreated material, but formic acid was an exception. The toxic effects on yeast were studied using concentrations corresponding to loadings of 12 and 20% total solids (TS). Among individual inhibitors that were quantitated in pretreatment liquids, the concentrations of formaldehyde were by far most toxic. There was no or minimal yeast growth in the formaldehyde concentration range (5.8–7.7 mM) corresponding to 12% TS.